2018
DOI: 10.1002/cam4.1549
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab maintenance therapy of follicular lymphoma in clinical practice

Abstract: Standard of care for patients with symptomatic, advanced‐stage follicular lymphoma (FL) is rituximab‐containing chemoimmunotherapy followed by rituximab maintenance. This prospective, multicenter, noninterventional study analyzed how efficacy and safety data from randomized controlled trials translate into clinical practice in Germany. Both treatment‐naïve and relapsed/refractory patients with FL, who responded to rituximab‐containing induction and were scheduled for rituximab maintenance, were observed for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, our data show an unexpected treatment pattern in FL patients with limited stage I/II disease accounting for about one quarter of the study cohort (Table 2). These patients may be cured with radio(immuno)therapy 29,30 but received chemoimmunotherapy with palliative intent, which is in line with findings from the NCLS study reported by Nastoupil et al 31 and the recently published RIM trial 32 . Interestingly, in our study, FL patients with limited disease were more prevalent in the private practice (30.8%) as compared to the hospital treatment setting (20.2%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our data show an unexpected treatment pattern in FL patients with limited stage I/II disease accounting for about one quarter of the study cohort (Table 2). These patients may be cured with radio(immuno)therapy 29,30 but received chemoimmunotherapy with palliative intent, which is in line with findings from the NCLS study reported by Nastoupil et al 31 and the recently published RIM trial 32 . Interestingly, in our study, FL patients with limited disease were more prevalent in the private practice (30.8%) as compared to the hospital treatment setting (20.2%).…”
Section: Discussionsupporting
confidence: 91%
“…These patients may be cured with radio(immuno)therapy 29 , 30 but received chemoimmunotherapy with palliative intent, which is in line with findings from the NCLS study reported by Nastoupil et al 31 and the recently published RIM trial. 32 Interestingly, in our study, FL patients with limited disease were more prevalent in the private practice (30.8%) as compared to the hospital treatment setting (20.2%). Our real‐world results together with findings from the RIM trial may suggest a shift from radiotherapy as recommended in current guidelines to early systemic treatment in this patient subgroup.…”
Section: Discussionmentioning
confidence: 47%
“…40,[44][45][46] In a systematic review and meta-analysis of RCTs, MR was associated with improved OS, primarily in the relapsed or refractory setting. 47 Several reports have recently described real-world 1L practices and outcomes in FL in relation to the use of MR. [48][49][50][51] For instance, a German study reported improvement in complete response rates with maintenance therapy, 48 whereas Nordic 49 and Czech 50,51 studies reported improvement in OS with MR. In contrast, the largest-and, to date, only-nationwide study of real-world FL practices and outcomes in the United States, the NLCS, 27 did not reveal an association between MR and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have recently described real‐world 1L practices and outcomes in FL in relation to the use of MR 48‐51 . For instance, a German study reported improvement in complete response rates with maintenance therapy, 48 whereas Nordic 49 and Czech 50,51 studies reported improvement in OS with MR.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance therapy has become a standard part of treatment. It has contributed to long term durable remissions and cures in other hematological diseases, such as acute lymphoblastic leukemia and follicular lymphoma, but its role in AML is still controversial. With the exception of arsenic trioxide and retinoic acid in acute promyelocytic leukemia, no maintenance therapy has demonstrated sufficient efficacy to be considered standard in the treatment of AML.…”
Section: Introductionmentioning
confidence: 99%